Obtención de los parámetros de funcionamiento de las turbinas, Michell Banki y Pelton, emplazadas en el laboratorio de máquinas hidráulicas del Área de la Energía, las Industrias y los Recursos Naturales no Renovables. - Gualán Quizhpe, Edwin Patricio (2013)
The present practical work, demonstrates the process of transformation of the hydraulic energy in mediating electric power the use of the turbines Michell Banki and Pelton, starting from the implementation of this turbines in the laboratory of hydraulic machines of the Area of the Energy, the Industries and the Natural Resources not Renewable of the National University of Loja. The parameters of operation of these turbines were determined, considering that this investigation will contribute in the academic formation, linking the theoretical one with the practice of the students of the careers of electromechanical engineering and technology in electricity, helping in the units of mechanics of fluids and hydraulic machines. It offers an important contribution to consolidate the Center of investigations of Renewable Energies and Energy (CIEREE) Efficiency that it is a specialized center that generates knowledge and development of technologies that cooperate to the energy local, regional and national sustainability, respecting the environment and supporting to the diversification of the energy womb of the Country. The use of the turbines Michell Banki and Pelton, allow to know and to develop dexterity, abilities on as to implant a small power station and to provide energy to an entire town. With examples of applications a guide of practices proposals was elaborated and developed so that the students can be guided and in the later thing they make use of these turbines with the purpose of generating electric power.